Complete chloroplast genome sequences of Dioscorea: Characterization, genomic resources, and phylogenetic analyses - Zhao, Zhenyu; Wang, Xin; Yu, Yi; Yuan, Subo; Jiang, Dan; Zhang, Yujun; Zhang, Teng; Zhong, Wenhao; Yuan, Qingjun; Huang, Luqi (PeerJ, 2018)
Dioscorea L., the largest genus of the family Dioscoreaceae with over 600 species, is not only an important food but also a medicinal plant. The identification and classification of Dioscorea L. is a rather difficult task. In this study, we sequenced five Dioscorea chloroplast genomes, and analyzed with four other chloroplast genomes of Dioscorea species from GenBank. The Dioscorea chloroplast genomes displayed the typical quadripartite structure of angiosperms, which consisted of a pair of inverted repeats separated by a large single-copy region, and a small single-copy region. The location and distribution of repeat sequences and microsatellites were determined, and the rapidly evolving chloroplast genome regions (trnK-trnQ, trnS-trnG, trnC-petN, trnE-trnT, petG-trnW-trnP, ndhF, trnL-rpl32, and ycf1) were detected. Phylogenetic relationships of Dioscorea inferred from chloroplast genomes obtained high support even in shortest internodes. Thus, chloroplast genome sequences provide potential molecular markers and genomic resources for phylogeny and species identification.
Keywords: Chloroplast genome; Dioscorea; Phylogeny; Single sequence repeats; Variable marker